Uma abordagem do ensino de congruência na educação básica - Gomes, Ataniel Rogério Gonçalves (2015)
The advent in 1801 of the brilliant work Disquisitiones Arithmeticae of Carl Gauss Friedrich (1777-1885) provided extremely important elements to Number Theory, including the study of congruences, which attracts the eyes of many mathematicians to this day for its application in various areas, including basic education issues, highlighting the need of their study as algebraic learning tool. Therefore, this paper proposes to approach the study of congruence in a systematic way, in order to the context of basic education, by proposing didactic sequence, and their application to everyday problems.